2003
DOI: 10.1159/000070945
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Nonscarring Subepidermal Blistering Disease Associated with Autoantibodies Reactive with Both Type VII Collagen and Laminin 5

Abstract: A 35-year-old Japanese woman had recurrent, pruritic, vesicular lesions on the face, neck and upper back as well as erosive lesions of the oral cavity and genitalia. The skin and mucosal lesions healed without scarring upon the systemic administration of corticosteroid and azathioprine. Direct immunofluorescence revealed linear deposits of IgG, IgA and C3 at the cutaneous basement membrane zone. Indirect immunofluorescence on 1 M NaCl-split human skin sections demonstrated that the patient’s IgG antibodies rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…While bullous disease patients with autoantibodies against multiple autoantigens (including L-332) in epidermal BM have been described, such patients are relatively rare [25][26][27][28][29][30] . In contrast, a recent study found that 29 of 72 patients with BP (40%) had circulating IgG reactive with L-332 by ELISA 9 .…”
Section: Discussionmentioning
confidence: 99%
“…While bullous disease patients with autoantibodies against multiple autoantigens (including L-332) in epidermal BM have been described, such patients are relatively rare [25][26][27][28][29][30] . In contrast, a recent study found that 29 of 72 patients with BP (40%) had circulating IgG reactive with L-332 by ELISA 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of autoantibodies to type VII collagen and laminin 5 or BP antigen has been reported [2,3,4,5]. On the other hand, anti-p200 pemphigoid complicated by another subepidermal autoimmune bullous disease is very rare.…”
Section: Discussionmentioning
confidence: 99%
“…The cases of subepidermal blistering disease associated with more than two antigens have rarely been reported [2,3,4,5]. We describe a case of a subepidermal blistering disease associated with autoantibodies to both type VII collagen and anti-p200 pemphigoid antigen (p200) which was accompanied with exfoliative esophagitis.…”
Section: Introductionmentioning
confidence: 99%
“…Several similar cases, however, have been previously reported. We have reported a nonscarring subepidermal blistering disease associated with autoantibodies reactive with both type VII collagen and laminin 5 that could be diagnosed as coexistence of EBA and cicatricial pemphigoid [3]. Jonkman et al [2] described a case of EBA with IgG autoantibodies against type VII collagen and laminin a 3 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that certain autoimmune bullous diseases may have double distinct autoantibodies against the skin in the same patient [1,2,3,4,5]. However, the pathophysiological significances of two distinct autoantibodies against the skin in an autoimmune bullous dermatosis are not fully understood.…”
Section: Introductionmentioning
confidence: 99%